Increased Amygdala and Visual Cortex Activity and Functional Connectivity towards Stimulus Novelty Is Associated with State Anxiety - Ousdal, Olga T.; Andreassen, Ole A.; Server, Andres; Jensen, Jimmy (PLOS ONE, 2014)
Novel stimuli often require a rapid reallocation of sensory processing resources to determine the significance of the event, and the appropriate behavioral response. Both the amygdala and the visual cortex are central elements of the neural circuitry responding to novelty, demonstrating increased activity to new as compared to highly familiarized stimuli. Further, these brain areas are intimately connected, and thus the amygdala may be a key region for directing sensory processing resources to novel events. Although knowledge regarding the neurocircuit of novelty detection is gradually increasing, we still lack a basic understanding of the conditions that are necessary and sufficient for novelty-specific responses in human amygdala and the visual cortices, and if these brain areas interact during detection of novelty. In the present study, we investigated the response of amygdala and the visual cortex to novelty, by comparing functional MRI activity between 1st and 2nd time presentation of a series of emotional faces in an event-related task. We observed a significant decrease in amygdala and visual cortex activity already after a single stimulus exposure. Interestingly, this decrease in responsiveness was less for subjects with a high score on state anxiety. Further, novel faces stimuli were associated with a relative increase in the functional coupling between the amygdala and the inferior occipital gyrus (BA 18). Thus, we suggest that amygdala is involved in fast sensory boosting that may be important for attention reallocation to novel events, and that the strength of this response depends on individual state anxiety.